Pengaruh Kebijakan Pengendalian Organisasi pada Proses dan Outcomes Negotiated Transfer Pricing - Gagaring Pagalung; Sekar Mayangsari (The Indonesian Journal of Accounting Research, 2013)
The objective of this study is to examine the effect of incentives and arbitration on the process and outcomes of negotiated transfer pricing. Two experiments were performed, one with high interdependence between the trading divisions, and the second with low interdependence. The result of this study showed that high interdependence using either incentives or arbitration was superior to using both. The other side, low interdependence using non-arbitration was superior to using of organizational control in negotiated transfer pricing.